Entrepreneurial leadership and school effectiveness in Zamfara state- Nigeria - Dahiru, Abbas Sani; Lope Pihie, Zaidatol Akmaliah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
Entrepreneurial leadership practice is an exclusive leadership practice that aid in confronting the tasks and challenges of organizations. However many questions had been raised on the influence of the leadership style in the educational settings. This paper explained the concepts of entrepreneurial leadership, school effectiveness, dimensions of entrepreneurial leadership, the role of entrepreneurial leadership in achieving school effectiveness. And finally the implications of the paper to the body of knowledge, policy makers and school principals were discussed in the paper.